U.S. public support for COVID-19 vaccine donation to low- and middle-income countries during the COVID-19 pandemic - Guidry, Jeanine P.D. (Vaccine, 2021)
As COVID-19 vaccines become available to the public, there will be a massive worldwide distribution effort. Vaccine distribution has historically been unequal primarily due to the inability of nations with developing economies to purchase enough vaccine to fully vaccinate their populations. Inequitable access to COVID-19 vaccines will not just cause humanitarian suffering, it will likely also be associated with increased economic suffering worldwide. This study focuses on the U.S. population and its beliefs about future COVID-19 vaccine donation by the U.S. to low- and middle-income countries. This study carried out a survey among 788 U.S. adults. Variables include demographics, COVID-19 vaccine priority status, COVID-19 vaccine donation beliefs, and Social Dominance Orientation. Analyses showed that older respondents were both less likely to endorse higher levels of COVID-19 vaccine donations and were more likely to want to wait until all in the U.S. who want the vaccine have received it; those who identified as Democrats were more likely to endorse higher levels of future COVID-19 vaccine donation than Republicans; and those scoring higher on SDO were both less likely to endorse higher levels of COVID-19 vaccine donations as well as more likely to want to wait until all in the U.S. who want the vaccine have received it. Policymakers, as well as healthcare providers and public health communication professionals, should give consideration to those messages most likely to engender support for global prevention efforts with each audience segment.